2022
DOI: 10.3389/fmars.2022.889840
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Time Series Sampling Reveals Thermal Variation and Shifts in Pseudo-nitzschia Species Composition That Contribute to Harmful Algal Blooms in an Eastern US Estuary

Abstract: In 2016-17, shellfish harvesting closed for the first time in Narragansett Bay, Rhode Island, USA, from domoic acid (DA), a neurotoxin produced by diatoms of the Pseudo-nitzschia genus. Pseudo-nitzschia have occurred frequently for over 60 years in Narragansett Bay’s Long-Term Plankton Time Series (NBPTS), therefore it is surprising that the first closure only recently occurred. Pseudo-nitzschia species are known to vary in their toxin production, thus species identification is critical for understanding the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Of the environmental factors we examined, temperature and light data were correlated ( r = 0.62) and thus could not both be included in the tb‐RDA. We chose to include temperature because it has been observed as a more important filter of phytoplankton composition than light in NBay (Karentz and Smayda 1984; Rynearson et al 2020; Roche et al 2022). The ordination analysis indicated that 80% of the variability in diatom ASV occurrence was constrained by axes one (64%) and two (16%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the environmental factors we examined, temperature and light data were correlated ( r = 0.62) and thus could not both be included in the tb‐RDA. We chose to include temperature because it has been observed as a more important filter of phytoplankton composition than light in NBay (Karentz and Smayda 1984; Rynearson et al 2020; Roche et al 2022). The ordination analysis indicated that 80% of the variability in diatom ASV occurrence was constrained by axes one (64%) and two (16%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the mass poisoning of wild marine animals, DA can cause significant economic damage to aquaculture farms [5,6]. Studies of the temporal dynamics of the Pseudo-nitzschia species associated with environmental or biotic factors or climate change events are carried out in highly productive waters or areas adjacent to aquaculture farms and recreational zones worldwide [7][8][9][10][11]. Such studies are crucial not only for interpreting the temporal patterns of the population dynamics of Pseudo-nitzschia but also for understanding the toxic events and their economic and social effects.…”
Section: Introductionmentioning
confidence: 99%